Pengaruh Intellectual Capital Terhadap Company Values Dengan Profitabilitas Sebagai Variabel Intervening - Baihaqqi, Mhd Anggi; Astuty, Widia; Sari, Maya (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2024)
This research was conducted with the aim of testing and analyzing the influence of Value Added Capital Employe, Value Added Human Capital, Structural Capital Value Added on company value through profitability in basic industrial and chemical companies listed on the Indonesia Stock Exchange directly or indirectly. The population in this research is all basic industrial and chemical companies listed on the Indonesia Stock Exchange. The sample used in this research was determined using a purposive sampling technique with the acquisition of 10 companies. This research approach uses associative research. The data collection technique uses documentation techniques, and the analysis techniques used are multiple linear regression analysis, hypothesis testing, coefficient of determination and part analysis. The research results show that testing the indirect influence hypothesis shows that Value Added Capital Employee, Value Added Human Capital, Structural Capital Value Added have no effect on company value through return on assets in basic industrial and chemical companies listed on the Indonesia Stock Exchange.Penelitian ini dilakukan dengan tujuan untuk menguji dan menganalisis pengaruh Value Added Capital Employe, Value Added Human Capital, Structural Capital Value Added terhadap Company Values melalui profitabilitas pada perusahaan indutri dasar dan kimia yang terdaftar di Bursa Efek Indonesia secara langsung mupun secara tidak langsung. Populasi dalam penelitian ini adalah seluruh perusahaan indutri dasar dan kimia yang terdaftar di Bursa Efek Indonesia. Sampel yang digunakan dipenelitian ini ditentukan dengan menggunakan teknik penarikan purposive sampling dengan perolehan 10 perusahaan. Pendekatan penelitian ini menggunakan penelitian asosiatif. Teknik pengumpulan data  menggunakan teknik dokumentasi, dan teknik analisis yang digunakan adalah analisis regresi linear berganda, pengujian hipotesis, koefisien determinasi dan part Analysis.  Hasil penelitian menunjukkan Pengujian hipotesis pengaruh tidak langsung menunjukkan Value Added Capital Employe, Value Added Human Capital, Structural Capital Value Added tidak berpengaruh terhadap Company Values melalui return on assets pada perusahaan industry dasar dan kimia yang terdaftar di Bursa Efek Indonesia.